Increasing Students’ Activeness by Using Hot Potatoes Strategy - Cahyani, Hesti Tri; Sumarni, Baiq (Jurnal Ilmiah IKIP Mataram, 2024)
This research aims to determine and analyze the increase in the activeness of class IXB students at SMP Negeri 5 Pringgabaya using the Hot Potatoes strategy. The subjects of this research were all 30 students in class IX B of SMP Negeri 5 Pringgabaya. The research method used is a mix of qualitative and quantitative methods. Data collection in this study used observation techniques, interviews and questionnaires. The research results show that the use of the hot potato learning strategy can increase student learning activeness. From the results of the researcher observations in cycle I, there were 2 aspects that were still low, namely oral activities and mental activities. It was found that there were still many students who lacked confidence in presenting discussion results and asked questions about things they did not understand. So in cycle II the teacher focuses more on approaching students and continues to motivate students to be active during the learning process so that low results can be improved in Cycle II. Approaching each student and asking students to ask each group, this can increase students activeness. Future researchers are advised to further deepen the Hot Potatoes learning strategy so that later when faced with a teaching situation they can apply it well. This is done because the Hot Potatoes strategy is not easy to implement but requires in-depth understanding so that this learning strategy can be implemented and provide maximum benefits.